"Femme, réveille-toi!" : Déclaration des droits de la femme et de la citoyenne et autres écrits - Gouges, Olympe de (Gallimard, 2014)
Femme, réveille-toi ; le tocsin de la raison se fait entendre dans tout l'univers ; reconnais tes droits. Le puissant empire de la nature n'est plus environné de préjugés, de fanatisme, de superstition et de mensonges. Le flambeau de la vérité a dissipé tous les nuages de la sottise et de l'usurpation. L'homme esclave a multiplié ses forces, a eu besoin de recourir aux tiennes pour briser ses fers. Devenu libre, il est devenu injuste envers sa compagne. Ô femmes! femmes, quand cesserez-vous d'être aveugles?" Un ton résolument frondeur, une langue énergique, un propos engagé, par l'une des grandes voix féminines de la Révolution française.
Première publication 1791
Keywords: 1700-1799; approches et analyses; citoyenneté; droits des femmes*; europe; fem1000; france; histoire et politique; incontournable; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; systèmes d'oppression; thématiques; violences

Sapphic fathers: Discourses of same-sex desire from nineteenth-century France - Schultz, Gretchen (University of Toronto Press, 2014)
Literature that explored female homosexuality flourished in late nineteenth-century France. Poets, novelists, and pornographers, whether Symbolists, Realists, or Decadents, were all part of this literary moment. In Sapphic Fathers, Gretchen Schultz explores how these male writers and their readers took lesbianism as a cipher for apprehensions about sex and gender during a time of social and political upheaval. Tracing this phenomenon through poetry (Baudelaire, Verlaine), erotica and the popular novel (Belot), and literary fiction (Zola, Maupassant, Péladan, Mendès), and into scientific treatises, Schultz demonstrates that the literary discourse on lesbianism became the basis for the scientific and medical understanding of female same-sex desire in France. She also shows that the cumulative impact of this discourse left tangible traces that lasted well beyond nineteenth-century France, persisting into twentieth-century America to become the basis of lesbian pulp fiction after the Second World War.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppression; thématiques; violences; états-unis; études littéraires